Strategi Perang antara Belanda Melawan Invasi Jepang di Palembang dan Dampaknya terhadap Lingkungan - Aderoben, Andromeda; Septiansi, Ira; Syarifuddin, Syarifuddin (Universitas Hamzanwadi, 2024)
The purpose of this study explains the Japanese attack strategy and Dutch defense and its impact on the environment in Palembang. The method used is the historical method by utilizing primary sources such as memoirs of historical actors, contemporaneous newspapers, as well as secondary sources such as books and scientific articles. This research also uses geography with an environmental perspective. The results show that Japan implemented a combined land, sea and air strategy with paratroopers as the main force to capture Palembang. Meanwhile, the Dutch focused on protecting airfields and oil refineries with scorched earth tactics if pressed. Environmental impacts of the conflict included air pollution from oil refinery fires and pollution of the Musi River by oil spills and war waste. The novelty of this research lies in the study of the environmental aspects of Japanese military operations in Palembang that have not been widely discussed before. This research provides a new perspective on the impact of war on the environment in a historical context.